A multicomponent, high-intensity, patient-centered care intervention to optimize transitional care coordination for complex multimorbid people: a pre-post design - del Pino-Sedeño, Tasmania; de León, Beatriz González; Hernández, Miguel García; Olmedo, Paula Coronil; Melián, Yeiza Semiramis Reyes; Hernández, Vanesa Martínez; Bautista, Estefanía García; Arraez, Encarnación Barrios; Cruz, Silvia Barreto; Abrante-Luis, Alejandra; García-Bello, Miguel Angel; González-Hernández, Yadira; et al. (Frontiers in Medicine, 2025)
IntroductionComplex multimorbid patients often experience uncoordinated care transitions, increasing the risk of poor adherence, fragmented care, and adverse outcomes. Multicomponent, patient-centered interventions may improve transitional care, but evidence remains limited and heterogeneous.MethodsThis pre-post intervention study evaluated the impact of SPICA, a multicomponent, high-intensity, patient-centered transitional care program implemented in Tenerife, Spain. Eligible adult patients with multimorbidity and complexity were consecutively enrolled between September 2023 and June 2024. Primary outcome was adherence to pharmacological treatment (Morisky Medication Adherence Scale-4). Secondary outcomes included patient satisfaction (Baker’s Questionnaire), health-related quality of life (HRQoL, EQ-5D-5L), disease (Disease Burden Morbidity Assessment), and treatment burden (Treatment Burden Questionnaire). Outcomes were assessed at baseline and one-month post-discharge. Multivariate linear regression was used for the satisfaction outcome, and bivariate models were conducted to explore predictors of the remaining intervention outcomes. McNemar’s Chi-squared test was used to evaluate changes in adherence rates, and ANCOVA models for other outcomes measured at both pre- and post-intervention.ResultsAmong the 112 patients, adherence improved from 53.4 to 84.9% (p < 0.001). Satisfaction with care was high (median 71; IQR 67–81). Significant improvements were observed in HRQoL (mobility [β − 0.56], pain/discomfort [β − 0.55], anxiety/depression [β − 0.37], EQ-5D Index [β 0.14], EQ-VAS [β 7.08]), and treatment burden (β − 12.24). Baseline scores were the most consistent predictors of improvement; age, sex, and comorbidity were not significant factors.DiscussionA multicomponent, high-intensity, patient-centered intervention such as SPICA appears to be associated with improvements in adherence and health outcomes in complex multimorbid patients transitioning from hospital to primary care, and may also be linked to high levels of patient satisfaction. Effects were more pronounced in those with worse baseline scores, suggesting a positive impact among those most in need. Nevertheless, further studies with more robust methodological designs are required to confirm these associations.